2021
DOI: 10.3390/antiox10060906
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 and Cardiovascular Diseases

Abstract: Coenzyme Q10 (CoQ10), which plays a key role in the electron transport chain by providing an adequate, efficient supply of energy, has another relevant function as an antioxidant, acting in mitochondria, other cell compartments, and plasma lipoproteins. CoQ10 deficiency is present in chronic and age-related diseases. In particular, in cardiovascular diseases (CVDs), there is a reduced bioavailability of CoQ10 since statins, one of the most common lipid-lowering drugs, inhibit the common pathway shared by CoQ10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 85 publications
0
28
0
1
Order By: Relevance
“…The antioxidant properties of CoQ10 also depend on its capacity in recycling other antioxidants such as vitamin C and vitamin E [ 162 ]. CoQ10 deficiency is found in chronic and age-related diseases.…”
Section: Mitochondrial Antioxidant Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidant properties of CoQ10 also depend on its capacity in recycling other antioxidants such as vitamin C and vitamin E [ 162 ]. CoQ10 deficiency is found in chronic and age-related diseases.…”
Section: Mitochondrial Antioxidant Systemmentioning
confidence: 99%
“…CoQ10 deficiency is found in chronic and age-related diseases. For instance, in cardiovascular diseases (CVDs), the reduced bioavailability of CoQ10 is because statins, one of the most common lipid-lowering drugs, inhibits the common pathway shared by CoQ10 endogenous biosynthesis and cholesterol biosynthesis [ 162 ].…”
Section: Mitochondrial Antioxidant Systemmentioning
confidence: 99%
“…Recent research showed that one MetDiet-style meal reduced the expression of proinflammatory molecules [29], the overall systemic inflammatory status [30], and several diseases associated with chronic low-grade inflammation. In adult individuals, a MetDiet intervention led to lower glycoxidative impairment [31] and inflammatory response [32,33]. A meta-analysis including 2300 subjects reported a significant reduction in high-sensitivity C-reactive protein (hs-CRP) (−0.98 mg/L, p < 0.0001), intracellular adhesion molecule-1 (−23.73 ng/mL, p = 0.008), and IL-6 (−0.42 pg/mL, p = 0.008) in individuals assigned to MetDiet, compared with those following a control intervention protocol [34].…”
Section: The Mediterranean Diet: a Healthy Dietary Pattern For People With Sars-cov-2 Infectionmentioning
confidence: 99%
“…Coenzyme Q10, also known as ubiquinone, is an organic chemical compound belonging to the group of quinones. Coenzyme Q10 was isolated by Festenstein et al (1955) and Crane et al (1957) [ 12 , 13 ]. Coenzyme Q10 is commonly found in cell membranes, especially mitochondrial membranes, in both reduced (ubiquinol) and oxidized (ubiquinone) forms.…”
Section: Coenzyme Q10—brief Biochemical Overviewmentioning
confidence: 99%
“…This compound enables the basic biochemical reactions that make the life of the organism possible [ 16 ]. Coenzyme Q10 has the ability to transfer electrons ( e− ), therefore its highest concentration occurs in organs characterized by intense energy transformations (concentration: heart (114 μg/g) > kidneys (66.5 μg/g) > liver (55 μg/g) > muscles > brain), because the most important role of this compound is to facilitate the production of adenosine triphosphate (ATP) in mitochondria ( Figure 3 ) [ 13 , 17 ]. Serum coenzyme Q10 concentration is approximately 1 μmol/L [ 18 ].…”
Section: Coenzyme Q10—brief Biochemical Overviewmentioning
confidence: 99%